2002
DOI: 10.5194/acp-2-67-2002
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric NO<sub>2</sub> columns: a comparison between model and retrieved data from GOME measurements

Abstract: Abstract. Tropospheric NO 2 plays a variety of significant roles in atmospheric chemistry. In the troposphere it is one of the most significant precursors of photochemical ozone (O 3 ) production and nitric acid (HNO 3 ). In this study tropospheric NO 2 columns were calculated by the fully coupled chemistry-climate model ECHAM4.L39(DLR)/CHEM. These have been compared with tropospheric NO 2 columns, retrieved using the tropospheric excess method from measurements by the Global Ozone Monitoring Experiment (GOME)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…This approach is based on the assumptions that a) stratospheric NO 2 does not depend on longitude, and that b) the reference region has a negligible tropospheric NO 2 burden. Tropospheric NO 2 columns from GOME have been validated against independent measurements (Heland et al, 2002), and have been extensively compared to model results (Velders et al 2001;Lauer et al 2002;Martin et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…This approach is based on the assumptions that a) stratospheric NO 2 does not depend on longitude, and that b) the reference region has a negligible tropospheric NO 2 burden. Tropospheric NO 2 columns from GOME have been validated against independent measurements (Heland et al, 2002), and have been extensively compared to model results (Velders et al 2001;Lauer et al 2002;Martin et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Lauer et al (2002) tended to have larger European columns than GOME in both January and July which they attribute to the absence of a sink for N 2 O 5 on aerosol in their model. Martin et al (2002) have better agreement than TOMCAT for July but in contrast to the TOMCAT model have lower NO 2 columns over Europe than the GOME data.…”
Section: Polluted Regionsmentioning
confidence: 99%
“…They found that the columns over Europe and North America were of the same order as those calculated by the MOZART model but were a factor of 2-3 higher over Asia. Lauer et al (2002) compared a climatological data set for NO 2 to the first 5 years of the GOME measurements. They examined the seasonal evolution of the column over Europe, the Eastern USA, Africa, South America, Australia and Southeast Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Velders et al (2001) compared these image-processing techniques with another approach for separating the tropospheric and stratospheric contributions, known as the reference sector or tropospheric excess method, and evaluated various aspects of the retrievals using output from the global chemistry transport models IM-AGES and MOZART. Two recent studies overestimated tropospheric NO 2 over polluted regions compared to GOME, but neglected hydrolysis of N 2 O 5 on tropospheric aerosols (Lauer et al, 2002;Savage et al, 2004). To give an indication of the importance of N 2 O 5 hydrolysis: Dentener and Crutzen (1993) showed that tropospheric NO x concentrations at middle and high latitudes could be reduced by up to 80% in winter and 20% in summer, and in the tropics and subtropics by 10-30%.…”
Section: Introductionmentioning
confidence: 99%